As Ligações Perigosas na literatura e no cinema: ponto de vista e construção de sentidos. - Terzakis, Philio Generino (2013)
This work aims at presenting the results of our research on point of view and the creation of meanings in the novel Dangerous liaisons, by Choderlos de Laclos, and in two of its film adaptations: Dangerous liaisons 1960 (1959), by Roger Vadim, and Dangerous liaisons (1988), by Stephen Frears. Throughout the work, we try to carry out a comparative analysis between the source text and its two hypertexts, focusing on the question of narrative perspective and the meanings this category produces. We started with a discussion of film adaptation of literary works, so as to confirm that the question of fidelity has long been overcome, having been replaced by a rather more coherent and necessary debate that concerning the sociology of adaptation, that is, the context in which the adaptations are materialized. From this point we try to present a concept and a classification of point of view that enabled us to analyze the selected narratives. The constructed theoretical support was used in the investigation of both the novel by Laclos and the adaptations by Vadim and Frears. Our initial hypothesis is that point of view is the most responsible element, in each work, for the elaboration of different meanings of evil. Taking into account the considerable relevance of narratives in our everyday life, we understand the fundamental role of critical analysis of values conveyed by such stories, from which derives the significance of our research. We hope the research transcends the proposed analysis so as also to contribute with further critical readings of narratives that inhabit our everyday life.